2016
DOI: 10.1038/ni.3462
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T cell receptor signaling by cholesterol sulfate, a naturally occurring derivative of membrane cholesterol

Abstract: Most adaptive immune responses require the activation of specific T cells through the T cell antigen receptor–CD3 complex (TCR). Here we show that cholesterol sulfate (CS), a naturally occurring analog of cholesterol, inhibits CD3 ITAM phosphorylation, a crucial first step in T cell activation. Biochemical studies show that CS disrupted TCR multimers, apparently by displacing cholesterol, known to bind TCRβ. Moreover, CS-deficient mice displayed a heightened sensitivity to a self-antigen, whereas increasing CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(133 citation statements)
references
References 50 publications
5
119
0
Order By: Relevance
“…The reasons for the CD8 + T cell specificity of this mechanism remain unclear. Interestingly, cholesterol sulfate, which is produced in vivo by the action of Sult2b1 upon cholesterol, disrupts TCR nanoclusters, decreases TCR avidity, and inhibits TCR signaling by displacing TCRβ-bound cholesterol [70]. The extent to which Sult2b1-derived cholesterol sulfate may serve as a dynamic negative feedback regulator of TCR activation in vivo is uncertain, but evidence does suggest that it plays a role in thymic selection through differential regulation of TCR signaling in thymic T cell subsets [70].…”
Section: Dynamic Sterol Fluxes Regulate T Cell Immunitymentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons for the CD8 + T cell specificity of this mechanism remain unclear. Interestingly, cholesterol sulfate, which is produced in vivo by the action of Sult2b1 upon cholesterol, disrupts TCR nanoclusters, decreases TCR avidity, and inhibits TCR signaling by displacing TCRβ-bound cholesterol [70]. The extent to which Sult2b1-derived cholesterol sulfate may serve as a dynamic negative feedback regulator of TCR activation in vivo is uncertain, but evidence does suggest that it plays a role in thymic selection through differential regulation of TCR signaling in thymic T cell subsets [70].…”
Section: Dynamic Sterol Fluxes Regulate T Cell Immunitymentioning
confidence: 99%
“…Interestingly, cholesterol sulfate, which is produced in vivo by the action of Sult2b1 upon cholesterol, disrupts TCR nanoclusters, decreases TCR avidity, and inhibits TCR signaling by displacing TCRβ-bound cholesterol [70]. The extent to which Sult2b1-derived cholesterol sulfate may serve as a dynamic negative feedback regulator of TCR activation in vivo is uncertain, but evidence does suggest that it plays a role in thymic selection through differential regulation of TCR signaling in thymic T cell subsets [70]. Adding yet further complexity to the picture, it was recently reported that cholesterol binding may serve a dual role in TCR signaling, promoting TCR avidity, but also restraining spontaneous signaling by keeping the TCR in an inactive allosteric conformation that cannot be phosphorylated [71].…”
Section: Dynamic Sterol Fluxes Regulate T Cell Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of ACAT1, a cholesterol esterification enzyme, led to increased CD8 + T cell cytotoxicity, TCR clustering, and TCR signaling (57). Further, cholesterol binds to the TCR-β chain (58), and the ratio of cholesterol to inhibitory cholesterol derivatives can potentiate TCR-mediated activation (59).…”
Section: Hfd Hyperlipidemia and Alloimmunitymentioning
confidence: 99%
“…In addition to the effects of cholesterol on T cell proliferation, mounting evidence suggests that cholesterol is involved in TCR mediated signal transduction. Cholesterol binds to the TCR-β chain (104), and the ratio of cholesterol to inhibitory cholesterol derivatives can potentiate TCR receptor mediated activation (105). …”
Section: Cholesterol In T Cell Activationmentioning
confidence: 99%